Impact of two light programs and two levels of dietary tryptophan for weanling piglets - Gomes, Lívea Maria [UNESP]; de Mello Miassi, Gabriela [UNESP]; Sousa dos Santos, Luan [UNESP]; Anton Dib Saleh, Mayra [UNESP]; Sartori, José Roberto [UNESP]; Panhoza Tse, Marcos Lívio [UNESP]; Antonio Berto, Dirlei [UNESP] (Elsevier, 2018)
Photoperiod and supplementary tryptophan can attenuate the effects of stressful weaning. However, few studies have evaluated tryptophan metabolism in the presence of light. This study aimed to evaluate the effects of tryptophan levels (TL) on the diet of weanling piglets submitted to different light programs (LP). Seventy-two piglets weaned at 21 days of age (starting weight 6.6 ± 2.33 kg) were used. The experimental design consisted of randomized blocks with 24 days of duration in a 2 × 2 factorial arrangement. Two LP were used: 12-h or 23-h light/day. Two digestible TL were used: 2.6 g or 5.2 g of Trp/kg feed on pre-starter I diet (from 0 to 14 trial days) and 2.4 g or 4.8 g of Trp/kg feed on pre-starter II diet (from 15 to 24 trial days). Six replicates of three animals per treatment were performed. Growth performance, blood glucose, plasma cortisol profiles and animal behavior were assessed. Blood glucose was measured on experimental days 0 and 24, and cortisol was measured on days 0 and 8. Behavior was observed on days 2, 9, 16 and 23. Neither growth performance nor blood glucose were affected by the interaction between LP and TL. The treatments did not influence daily weight gain, daily feed intake and blood glucose during the periods of 0–14, and 0–24 days. Feed:gain ratio improved during the 0–14 days period for piglets receiving 12-h light/day. The treatments did not influence the frequency of “moving” behaviors. However, the interaction between LP and TL affected the plasma cortisol and frequency of “feeding” and “lying” behaviors. Piglets that received the highest TL had lower plasma cortisol levels, reduced “feeding” behaviors and increased “lying” behaviors, compared to animals that received normal TL, when subjected to LP of 23-h light/day. The results suggest that use of LP of 23 h light/day is not indicated for piglets.
Keywords: Amino acid; Feeding behavior; Photoperiod; Swine; Welfare